The Impact of Strategic Leadership on The Effectiveness of Crisis Management: An exploratory study in the Iraqi Ministry of Health - Hasan, Amal Mansoor; Allaami, Shahlaa Ali; Asmael, Lena Omran (Journal of Risk and Crisis Management, 2022)
A crisis is an unexpected and sudden event, in which the strategic gap is highlighted due to the lack of adaptation to the changes that occur in the organization’s environment. The crisis leads to rapid organizational change, volatile economic conditions, problems for employees, unexpected technological changes and political effects, so the research objective is to determine the reality Representative strategic leadership (strategic personality, strategic thinking, strategic change, and strategic decisions) and the effectiveness of represented crisis management (response decision-making, communication and information flow, gather and resource mobilization) in the Iraqi Ministry of Health by analyzing the sample’s answers of the departments’ heads and people in the ministry amounted to ( 56) employee, where the research found that there is a statistical impact of strategic leadership in all its dimensions in the effectiveness of crisis management, and the research recommended the need to increase the ministry’s ability to learn from previous crises by analyzing its previous performance and the reasons for its previous failures and evaluating the adequacy and effectiveness of previous crisis management plans and programs with the intention of improving them. its plans and practices in managing the crisis with other countries or institutions and integrating lessons learned into its management plans as well as documenting and storing the knowledge obtained from the experience of dealing with previous crises.